2017
DOI: 10.25040/ecpb2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Skeletal Muscle Strength, Fatigue and Respiratory Efficiency in Young Healthy Females during Different Phases of Menstrual Cycle

Abstract: Introduction. Physiological functions of women are different from men. Though the muscle strength of women is lesser than in men, their engagement in sports is markedly increased and is equal to man nowadays. Females are more prone for sports related injuries compared to males [1]. Young females have lot of restrictions in developing countries like India for participation in sports [2]. Fluctuating levels of sex steroids affect the sensory-motor association in females [3]. Fluctuating levels of sex steroids du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, according to Slotkin (2004), the organophosphates have additional effects on brain development that may overshadow their cholinergic component. In addition, Priyadharshini et al (2017) found in their study that chronic exposure to organophosphate pesticides do affect the cardio respiratory system among farmers. About neonicotinoids, environmental exposure may lead to typical cardiovascular and nervous symptoms (Taira 2014).…”
Section: Short Term Effects/acute Effectsmentioning
confidence: 99%
“…Moreover, according to Slotkin (2004), the organophosphates have additional effects on brain development that may overshadow their cholinergic component. In addition, Priyadharshini et al (2017) found in their study that chronic exposure to organophosphate pesticides do affect the cardio respiratory system among farmers. About neonicotinoids, environmental exposure may lead to typical cardiovascular and nervous symptoms (Taira 2014).…”
Section: Short Term Effects/acute Effectsmentioning
confidence: 99%